2013
DOI: 10.4321/s1886-36552013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of written advertising material distributed through community pharmacies in Riyadh, Saudi Arabia

Abstract: BackgroundAdvertising is a crucial component of pharmaceutical industry promotion. Research indicates that information on advertisement materials might be inadequate, inaccurate, biased, and misleading.ObjectiveTo analyse and critically assess the information presented in print pharmaceutical advertisements in Saudi Arabia.MethodsPharmaceutical advertisements were collected from 280 community pharmacies in Riyadh city, Saudi Arabia. The advertisements were evaluated using criteria derived from the Saudi Food a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The least frequently found information are those concerning drug interactions (20%), the name of their active ingredients (22%), precautions or contraindications (24%) and side effects (26%). These results are consistent to those found in other studies [5,8,19,28,30,[33][34][35][36]. They are probably due to the fact that pharmaceutical companies tend to present information showing the drug efficacy and avoid highlighting the info on its safety of side effects.…”
Section: Discussionsupporting
confidence: 92%
“…The least frequently found information are those concerning drug interactions (20%), the name of their active ingredients (22%), precautions or contraindications (24%) and side effects (26%). These results are consistent to those found in other studies [5,8,19,28,30,[33][34][35][36]. They are probably due to the fact that pharmaceutical companies tend to present information showing the drug efficacy and avoid highlighting the info on its safety of side effects.…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that there was a significant mentioning of the brand name of the product (100%), its active ingredient and indication (100%), drug dosing (88%) and the site of marketing authorization holder (84%) in the brochures of generic pharmaceutical companies in Iraq, a similar finding was obtained through evaluation of brochures in Saudi Arabia and Nepal. [ 12 15 ] The result of this study also showed that there is a significant absence of mentioning excipent (15%), and drug–drug interaction (30%) in the evaluated brochures, similarly in India, there is a significant lack of excipent mentioning in brochures,[ 16 ] while drug-drug interaction was mentioned in only 33% of examined brochures that were given to Libyan physicians. [ 17 ]…”
Section: Discussionmentioning
confidence: 64%
“…These results are matching to the findings of other researchers. [16][17][18][19][20][21][22][23][24] Some other authors, arrived at even a darker picture; where they put it: "adverse reactions, warnings about interactions and contra-indications, were absent from all promotional printed materials studied." 20 Other researchers advised that, "Physicians should be cautious about drawing conclusions based on data presented on brochures provided by pharmaceutical companies."…”
Section: -15mentioning
confidence: 99%
“…29 Accordingly, they might not be of much help to the healthcare providers, to firmly rely on, if rational use of such medications is to be practiced. 22 As, the promoting companies themselves were feeling the inadequacy of the medication information they provide in their brochures, many pharmaceutical promotional brochures contain a footnote showing the contact address of the promoting companies encouraging interested healthcare providers to contact them if they might ever need more information about the promoted products. Pakistani researchers studying these encouraging invitations, reported very weak responses, from those companies, to such written requests from doctors.…”
Section: -15mentioning
confidence: 99%